Innovative strategies for assessing the management of variable economic development of enterprises - Fatalov, V.; Wu Qian (Економічний вісник Донбасу, 2024)
The modern economic landscape is characterised by a high level of dynamism, which necessitates the use of innovative strategies for managing the development of enterprises. The article considers the issues of evaluating the efficiency of managing the variable economic development of enterprises, which involves analysing alternative strategies and adapting to changes in the external environment. It has been determined that traditional approaches to evaluating the effectiveness of management decisions often do not take into account the multi-vector development of enterprises, which can limit their competitiveness in the long term. The study substantiates the need to apply innovative evaluation methods, in particular, the integration of digital technologies, artificial intelligence and big data analytics into management decision-making processes. The emphasis is placed on the use of forecasting models that allow to assess the probability of success of alternative development strategies and their impact on the financial stability of enterprises. A system of criteria for assessing the effectiveness of variable economic development is proposed, which covers not only financial indicators, but also the level of technological innovation, resilience to crisis phenomena and the ability to scale business processes. Special attention is paid to the practical aspects of implementing innovative assessment strategies. Real cases of applying digital platforms and machine learning algorithms for monitoring and analysing the economic development of enterprises are considered. It is proved that the use of adaptive valuation models can reduce the risks associated with the uncertainty of the market environment, as well as increase the flexibility and efficiency of management decisions. The results of the study can be useful for business executives, analysts, strategic managers and researchers who are engaged in assessing the effectiveness of management under conditions of uncertainty. The proposed approaches help to optimise management processes, increase the competitiveness of enterprises and ensure their sustainable development in the long term.